Internationalization of a SME: Multivision, Lda - Rodrigues, Ana Sofia da Silva (2019)
With the Portuguese IT consultancy market entering in a phase of saturation as well as the fierce competition among the companies on the market, internationalization is a key economic indicator (and success factor) to achieve and maintain a healthy market share and growth potential. This thesis objective is to analyze the internationalization phenomenon from a strategic point of view, while presenting the project of a business plan to internationalize the IT consultancy company "Multivision, Lda". Fundamentally, this project is focused on finding the best-fit strategy to internationalize business including the locations / countries most appropriate to be focused on from the company´s portfolio. The main dynamics of an internationalization process are examined - from a theoretical point of view first and then adapting this framework to the company's environment. A qualitative research was performed, mainly consisting of information provided by the Financial Manager of the company and information provided by the internationalization project PT2020. In order to analyze the internationalization of a SME, the understanding of the bestfitted criteria for the identification of target markets, their market-entry barriers as well as the company´s operational strategy are key factors. One believes that studying this theme, the understanding of the criteria needed to make the best choice of target markets, entry mode decisions and the operational strategy is implied. Through the development of the internationalization project of "Multivision, Lda", the author realized that this process is an always more relevant technique in the world of Small and Medium Enterprises, in order for companies to develop their business or even to be able to remain in the market.